The sisterhood of the traveling pants 2 [videorecording (DVD)] - Hamri, Sanaa; Tamblyn, Amber; Ferrera, America, 1984-; Lively, Blake; Brashares, Ann (Distributed by Warner Home Video, 2008)
Join the four best friends as they finish their first year of college and dive into a summer of excitement. Bridget journeys to Turkey on an archeological dig. Carmen plunges into the hectic, creative world of summer theater in Vermont. Lena discovers new love and old heartbreak at the Rhode Island School of Design. Tibby takes a big step in her relationship with Brian in the Big Apple.